Understanding DMG: current treatment options and prospective solutions using nanoparticles - Ahmed Mohamed; Aleksey Lyzlov; Rachna Prasad; Rex A. Moats; Mark D. Krieger; Virendra R. Desai; Ashley S. Margol; Peter A. Chiarelli; Meenakshi Upreti (Drug Delivery and Translational Research, 2026)

Interspecific interaction, habitat, or neighborhood occupancy? Long-term dataset reveals factors influencing the barred owl invasion through time - Kaitlin R. McGee; Alan B. Franklin; Peter C. Carlson; Angela Rex; Paul Doherty, Jr. (Biological Conservation, 2026)

Effect of short-term storage on sperm quality and microbiome dynamics in blue catfish, Ictalurus furcatus - Samitha S.N. Liyanage; Kasun A. Bandara; Kaylan A. Martin; Kyle R. Wood; Jason W. Abernathy; Benjamin H. Beck; Timothy J. Bruce; Luke A. Roy; Rex A. Dunham; Xu Wang; Ian A.E. Butts (Aquaculture, 2026)

Cryopreservation techniques for blue catfish, Ictalurus furcatus, sperm using 2.5 mL straws - Kyle R. Wood; Brian Bosworth; Samitha S.N. Liyanage; Alexandra E. Nowicki; Kaylan A. Martin; Rex A. Dunham; Benjamin H. Beck; Jason W. Abernathy; Xu Wang; Luke A. Roy; Ian A.E. Butts (Cryobiology, 2025)

Parental impacts on industry-relevant offspring performance traits using blue catfish, Ictalurus furcatus (Valenciennes, 1840), cryopreserved sperm - Kyle R. Wood; Ying Zhang; V. MacKenzie Tackett; Kaylan A. Martin; Samitha S.N. Liyanage; Benjamin H. Beck; Jason W. Abernathy; Rex A. Dunham; Luke A. Roy; Xu Wang; Ian A.E. Butts (Theriogenology, 2025)

Precision forestry in actively managed loblolly pine plantations: Leaf area index response one growing season following a variable-rate fertilization - Chris W. Cohrs; Al Lyons; Timothy J. Albaugh; David R. Carter; Otávio C. Campoe; Rafael A. Rubilar; Matthew Sumnall; Andrew Trlica; Mark V. Corrao; Simerjeet Virk; Rex Lester; Rachel L. Cook (Forest Ecology and Management, 2025)

Sperm fatty acid composition as an indicator of quality and cryotolerance in blue catfish, Ictalurus furcatus - Kyle R. Wood; Matthew K. Litvak; Samitha S.N. Liyanage; Kaylan A. Martin; V. MacKenzie Tackett; Rex A. Dunham; Luke A. Roy; Cynthia K. Faulk; Benjamin H. Beck; Jason W. Abernathy; Xu Wang; Ian A.E. Butts (Theriogenology, 2025)

P30-81 High-throughput RNA sequencing (Transcriptomics) combined with multiparametric New Approach Methodologies (NAMs) for cardiotoxicity risk assessment and mechanistic determination - J. Eakins; C. Bruhn; A. Rosell-Hildago; R. Rex; D. Yuezak; M. Fernandes dos Reis; T. Samatov; A. Hackmann; G.R. Aquino; C. Vogeley; N. Sahini; G. Goussarov; et al. (Toxicology Letters, 2025)

Biosolids-derived phosphorus persists in Florida sandy soils - JoAnn B. Donald; Robert G. Hatfield; Rex Ellis; Todd Z. Osborne; Allan R. Bacon; Yang Lin (Geoderma Regional, 2025)

P06-21 Multiparametric in vitro assays combined with high-throughput RNA sequencing for cardiotoxicity risk assessment and mechanistic insight - S. Llewellyn; A. Rosell-Hidalgo; C. Bruhn; K. Headspith; T. Samatov; A. Hackmann; G.R. Aquino; M. Fernandes dos Reis; R. Rex; D. Yuezak; C. Vogeley; N. Sahini; et al. (Toxicology Letters, 2024)

Co-pyrolysis of real-world plastics polystyrene, polypropylene and low-density polyethylene, its thermal behaviour and kinetic studies - P. Rex; L. R. Miranda (International Journal of Environmental Science and Technology, 2024)

Molecular biomarkers for sperm quality in an economically important fish: Blue catfish, Ictalurus furcatus - Hana N. Hess; Marie E. Strader; Helen R. Montague; Timothy J. Bruce; Gavin L. Aguilar; Sune R. Sørensen; Laura E. Jenkins; Luke A. Roy; Rex A. Dunham; Ian A.E. Butts (Aquaculture, 2024)

In vitro fertilization with frozen-thawed blue catfish (Ictalurus furcatus) sperm and implications for gene banking - Helen R. Montague; Hana N. Hess; V. MacKenzie Tackett; Savannah L. Britt; Larry L. Lawson; Gavin L. Aguilar; Laura E. Jenkins; Luke A. Roy; Leigh W. Holland; Rex A. Dunham; Matthew K. Litvak; Ian A.E. Butts (Aquaculture, 2023)

Discovery of pyrrolo[2,1-f][1,2,4]triazine-based inhibitors of adaptor protein 2-associated kinase 1 for the treatment of pain - Carolyn D. Dzierba; Bireshwar Dasgupta; George Karageorge; Walter Kostich; Brian Hamman; Jason Allen; Kim M. Esposito; Ramesh Padmanabha; James Grace; Kimberley Lentz; John Morrison; Daniel Morgan; et al. (Medicinal Chemistry Research, 2023)

Experimental investigation on the effects of shoreface nourishment placement and timing on long-term cross-shore profile development - Bjarke Eltard Larsen; Dominic A. van der A; Rex Carstensen; Stefan Carstensen; David R. Fuhrman (Coastal Engineering, 2023)

Ecological and genomic analyses of candidate phylum WPS ‐2 bacteria in an unvegetated soil - Andriy Sheremet; Gareth M. Jones; Jessica Jarett; Robert M. Bowers; Isaac Bedard; Cassandra Culham; Emiley A. Eloe‐Fadrosh; Natalia Ivanova; Rex R. Malmstrom; Stephen E. Grasby; Tanja Woyke; Peter F. Dunfield (Environmental Microbiology, 2020)
Summary Members of the bacterial candidate phylum WPS‐2 (or Eremiobacterota) are abundant in several dry, bare soil environments. In a bare soil deposited by an extinct iron–sulfur spring, we found that WPS‐2 comprised up to 24% of the bacterial community and up to 10 8 cells per g of soil based on 16S rRNA gene sequencing and quantification. A single genus‐level cluster ( Ca. Rubrimentiphilum) predominated in bare soils but was less abundant in adjacent forest. Nearly complete genomes of Ca. Rubrimentiphilum were recovered as single amplified genomes (SAGs) and metagenome‐assembled genomes (MAGs). Surprisingly, given the abundance of WPS‐2 in bare soils, the genomes did not indicate any capacity for autotrophy, phototrophy, or trace gas metabolism. Instead, they suggest a predominantly aerobic organoheterotrophic lifestyle, perhaps based on scavenging amino acids, nucleotides, and complex oligopeptides, along with lithotrophic capacity on thiosulfate. Network analyses of the entire community showed that some species of Chloroflexi , Actinobacteria , and candidate phylum AD3 (or Dormibacterota) co‐occurred with Ca. Rubrimentiphilum and may represent ecological or metabolic partners. We propose that Ca. Rubrimentiphilum act as efficient heterotrophic scavengers. Combined with previous studies, these data suggest that the phylum WPS‐2 includes bacteria with diverse metabolic capabilities.

Using high-resolution Pb isotopes to unravel the petrogenesis of Sakurajima volcano, Japan - Joshua R. Brown; Rex N. Taylor; Masato Iguchi (Bulletin of Volcanology, 2020)
Sakurajima volcano on the rim of Aira caldera erupts daily, threatening the major nearby population centre of Kagoshima. Before 1955, eruptions have typically consisted of intermittent Plinian and effusive activity, but since 1955, frequent Vulcanian explosions have occurred, indicating a change in pre-eruptive processes. High-resolution Pb isotopes are used here to constrain the components, including crustal assimilants, and petrogenetic processes contributing to the composition of both pre and post 1955 magmas. Sakurajima eruptive products have more radiogenic Pb ( 206 Pb/ 204 Pb = 18.40–18.42) than nearby Sumiyoshiike basalts ( 206 Pb/ 204 Pb = 18.24), a proxy for the primitive magma feeding the Sakurajima-Aira system. Sakurajima samples lie along a mixing line between these basalts and locally exposed crustal compositions. Their Pb isotopes are consistent with addition of ~ 5% average crustal melt to the primitive basaltic magma. The narrow range of Pb isotope ratios, despite variable SiO 2 contents (56.6–72.3 wt%), suggests that the final erupted magmas are derived from fractional crystallization of a mafic precursory magma displaying relatively consistent levels of crustal contamination. Andesites erupted between 4–3.7 ka and the 1995 eruption are contaminated to a greater extent, indicating that magmas with distinct compositions can feed phases of activity or individual eruptions. Post 1955 andesitic pyroclastics have lower SiO 2 and higher MgO than older lavas, yet equivalent Pb isotope ratios. The more mafic composition of post 1955 eruptive products can be attributed to increased throughput of mafic magma to the system.

The Bacterial Symbiont Phaeobacter inhibens Shapes the Life History of Its Algal Host Emiliania huxleyi - Anna R. Bramucci; Leen Labeeuw; Fabini D. Orata; Elizabeth M. Ryan; Rex R. Malmstrom; Rebecca J. Case (Frontiers in Marine Science, 2018)

Relations between work and upper extremity musculoskeletal problems (UEMSP) and the moderating role of psychosocial work factors on the relation between computer work and UEMSP - Nektaria Nicolakakis; Susan R. Stock; Michal Abrahamowicz; Rex Kline; Karen Messing (International Archives of Occupational and Environmental Health, 2017)

Nestedness and species replacement along bathymetric gradients in the deep sea reflect productivity: a test with polychaete assemblages in the oligotrophic north‐west Gulf of Mexico - Carol T. Stuart; Solange Brault; Gilbert T. Rowe; Chih‐Lin Wei; Martine Wagstaff; Craig R. McClain; Michael A. Rex (Journal of Biogeography, 2017)
Aim To test the hypothesis that low productivity drives the nestedness component of β‐diversity in polychaetes at the deep‐sea floor. Location Western Gulf of Mexico. Methods We used A. Baselga's (2010, Global Ecology and Biogeography, 19 , 134–143) metrics of species replacement and nestedness to assess their overall significance with differences in depth and particulate organic carbon ( POC ) flux to the seafloor. We used M. A. Rodríguez‐Gironés & L. Santamaría's (2006, Journal of Biogeography , 33 , 924–935) BINMATNEST to calculate the significance and direction of nestedness with depth and POC flux. Results Nestedness was the most significant part of β‐diversity with depth and POC flux. The rank order of nestedness increased significantly with increasing depth, and decreased significantly with increasing POC flux. There was little endemism below 2000 m. Main conclusion The polychaete fauna in the deepest western Gulf of Mexico is largely a nested subset of the shallower upper to mid‐bathyal fauna. While the causes of β‐diversity in the deep sea are undoubtedly multivariate, the relative importance of turnover and nestedness appears to be modulated by productivity in the form of POC flux to the seafloor. Under circumstances of extremely low POC flux and animal density in the deepest reaches of the Gulf, nestedness may be caused by some populations being maintained by immigration from larger populations upslope, or by biogeographic filtering for tolerance to abyssal conditions. Resources at great depths in regions of exceptionally low productivity may be too limited to permit adaptation resulting in endemism and continued downslope turnover. If productivity helps to explain the nestedness part of β‐diversity, this may lead to a more unified theory of deep‐sea biodiversity.

Large‐scale maps of variable infection efficiencies in aquatic Bacteroidetes phage‐host model systems - Karin Holmfeldt; Natalie Solonenko; Cristina Howard‐Varona; Mario Moreno; Rex R. Malmstrom; Matthew J. Blow; Matthew B. Sullivan (Environmental Microbiology, 2016)
Summary Microbes drive ecosystem functioning and their viruses modulate these impacts through mortality, gene transfer and metabolic reprogramming. Despite the importance of virus‐host interactions and likely variable infection efficiencies of individual phages across hosts, such variability is seldom quantified. Here, we quantify infection efficiencies of 38 phages against 19 host strains in aquatic Cellulophaga ( Bacteroidetes ) phage‐host model systems. Binary data revealed that some phages infected only one strain while others infected 17, whereas quantitative data revealed that efficiency of infection could vary 10 orders of magnitude, even among phages within one population. This provides a baseline for understanding and modeling intrapopulation host range variation. Genera specific host ranges were also informative. For example, the Cellulophaga Microviridae , showed a markedly broader intra‐species host range than previously observed in Escherichia coli systems. Further, one phage genus, Cba41, was examined to investigate nonheritable changes in plating efficiency and burst size that depended on which host strain it most recently infected. While consistent with host modification of phage DNA, no differences in nucleotide sequence or DNA modifications were detected, leaving the observation repeatable, but the mechanism unresolved. Overall, this study highlights the importance of quantitatively considering replication variations in studies of phage–host interactions.

Gut microbiome composition and metabolomic profiles of wild western lowland gorillas ( Gorilla gorilla gorilla ) reflect host ecology - Andres Gomez; Klara Petrzelkova; Carl J. Yeoman; Klara Vlckova; Jakub Mrázek; Ingrid Koppova; Franck Carbonero; Alexander Ulanov; David Modry; Angelique Todd; Manolito Torralba; Karen E. Nelson; et al. (Molecular Ecology, 2015)
The metabolic activities of gut microbes significantly influence host physiology; thus, characterizing the forces that modulate this micro‐ecosystem is key to understanding mammalian biology and fitness. To investigate the gut microbiome of wild primates and determine how these microbial communities respond to the host's external environment, we characterized faecal bacterial communities and, for the first time, gut metabolomes of four wild lowland gorilla groups in the Dzanga‐Sangha Protected Areas, Central African Republic. Results show that geographical range may be an important modulator of the gut microbiomes and metabolomes of these gorilla groups. Distinctions seemed to relate to feeding behaviour, implying energy harvest through increased fruit consumption or fermentation of highly fibrous foods. These observations were supported by differential abundance of metabolites and bacterial taxa associated with the metabolism of cellulose, phenolics, organic acids, simple sugars, lipids and sterols between gorillas occupying different geographical ranges. Additionally, the gut microbiomes of a gorilla group under increased anthropogenic pressure could always be distinguished from that of all other groups. By characterizing the interplay between environment, behaviour, diet and symbiotic gut microbes, we present an alternative perspective on primate ecology and on the forces that shape the gut microbiomes of wild primates from an evolutionary context.

A genome- and phenome-wide association study to identify genetic variants influencing platelet count and volume and their pleiotropic effects - Khader Shameer; Joshua C. Denny; Keyue Ding; Hayan Jouni; David R. Crosslin; Mariza de Andrade; Christopher G. Chute; Peggy Peissig; Jennifer A. Pacheco; Rongling Li; Lisa Bastarache; Abel N. Kho; et al. (Human Genetics, 2014)

Food webs in Mediterranean rivers - Mary E. Power; Joseph R. Holomuzki; Rex L. Lowe (Hydrobiologia, 2013)

Elevated species diversity in abyssal gastropods off Newfoundland: the potential role of food supply - Carol T. Stuart; Michael A. Rex; Derek P. Tittensor; Craig R. Smith (Marine Biodiversity, 2011)

Nonmuscle myosin IIA with a GFP fused to the N-terminus of the regulatory light chain is regulated normally - Andras Kengyel; Wendy A. Wolf; Rex L. Chisholm; James R. Sellers (Journal of Muscle Research and Cell Motility, 2010)

Understanding the relation between Arctic ozone loss and the volume of polar stratospheric clouds - N. R. P. Harris; R. Lehmann; M. Rex; P. Von Der Gathen (International Journal of Remote Sensing, 2009)

Spatiotemporal patterns of wetland occurrence in the Prairie Pothole Region of eastern South Dakota - Sharon N. Kahara; Rachel M. Mockler; Kenneth F. Higgins; Steven R. Chipps; Rex R. Johnson (Wetlands, 2009)

Inferring the diversification of the epiphytic fern genus Serpocaulon (Polypodiaceae) in South America using chloroplast sequences and amplified fragment length polymorphisms - H.-P. Kreier; M. Rex; K. Weising; M. Kessler; A. R. Smith; H. Schneider (Plant Systematics and Evolution, 2008)

Nutrient routing in omnivorous animals tracked by stable carbon isotopes in tissue and exhaled breath - Christian C. Voigt; Katja Rex; Robert H. Michener; John R. Speakman (Oecologia, 2008)

Bat breath reveals metabolic substrate use in free-ranging vampires - Christian C. Voigt; Patricia Grasse; Katja Rex; Stefan K. Hetz; John R. Speakman (Journal of Comparative Physiology B, 2008)

Multicenter retrospective development and validation of a clinical prediction rule for nosocomial invasive candidiasis in the intensive care setting - L. Ostrosky-Zeichner; C. Sable; J. Sobel; B. D. Alexander; G. Donowitz; V. Kan; C. A. Kauffman; D. Kett; R. A. Larsen; V. Morrison; M. Nucci; P. G. Pappas; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Standing stocks and activity of Archaea and Bacteria in the western Arctic Ocean - David L. Kirchman; Hila Elifantz; Ana I. Dittel; Rex R. Malmstrom; Matthew T. Cottrell (Limnology and Oceanography, 2007)
This study examined the abundance, cell size, and activity of Bacteria and Archaea in the Chukchi Sea and the Canada Basin of the western Arctic Ocean in the spring (May—June) and summer (July—August) of 2002 and 2004. Data from fluorescence in situ hybridization (FISH) analyses indicate that bacterial abundance as a percent of total prokaryotes decreased with depth, whereas in contrast, Crenarchaeota increased from about 10%of prokaryotes in surface waters to as much as 40% in samples from 100 to 200 m. Euryarchaeota were detectable in only a few samples. Relative abundance of Crenarchaeota, expressed as a percent of total prokaryotes, correlated with ammonium concentrations, but relative bacterial abundance did not. Crenarchaeota cells were significantly larger than Bacteria by 1.5‐ to 2‐fold in the upper 200 m. Data collected from a combination of FISH and microautoradiography indicate that often the fraction of both Bacteria and Crenarchaeota assimilating organic compounds was high (up to 55%), and both microbial groups were more active in assimilating amino acids than other compounds. However, Crenarchaeota were usually less active than Bacteria in assimilating amino acids and glucose, but were nearly as active as Bacteria in assimilating protein and diatom extracellular polymers. The fraction of Bacteria and Crenarchaeota assimilating CO 2 in surface waters was higher than expected by anaplerotic fixation alone, suggesting that many of these microbes are chemoautotrophic. These data add to a growing body of evidence indicating how the roles of Archaea and Bacteria differ in biogeochemical cycles of the oceans.

Comparing herbivory effects of stream macroinvertebrates on microalgal patch structure and recovery - Joseph R. Holomuzki; Rex L. Lowe; Jennifer A. Ress (New Zealand Journal of Marine and Freshwater Research, 2006)
We studied short‐term herbivory and recovery of microalgal communities grazed by snails ( Potamopyrgus antipodarum ) , mayflies ( Deleatidium spp.), and caddisflies ( Pycnocentrodes aeris ) in microcosms containing low algal food supplies characteristic of grazer‐controlled streams. Herbivore biomass was standardised across single‐species treatments to assess grazing effects owing to taxon‐specific differences in feeding modalities. Potamopyrgus decreased algal biovolumes, on average, by 56% in 4 days, and multidimensional scaling (MDS) showed that snail‐grazed microalgal communities were distinct. The erect diatoms Synedra ulna and Staurosirella leptostauron were less abundant, and basal cells of the chlorophyte Stigeoclonium lubricum were more abundant, in snail‐containing treatments than in ungrazed controls and other species treatments. In contrast, more mobile caddisfly and mayfly larvae failed to significantly alter algal biomass and assemblage, suggesting radular mouthparts of snails were more effective at removing algae from the diatom‐dominated communities than the bladelike or brushing mouthparts of caddisflies and mayflies, respectively. Microalgal communities recovered to pre‐grazed conditions in all treatments after 4 days in a grazer‐free, outdoor flume. Diatoms also dominated the recovery phase, but the erect forms S. ulna and S. leptostauron were more abundant during recovery than grazing. Wilhm's diversity decreased after recovery, suggesting grazing had a positive effect on algal diversity. Thus, herbivory primarily by Potamopyrgus affected microalgal patch structure, and hence the starting successional sere, but had no detectable effect on short‐term successional direction in these fast‐recovering communities.

Bathymetric and geographic population structure in the pan‐Atlantic deep‐sea bivalve Deminucula atacellana (Schenck, 1939) - JOHN D. ZARDUS; RON J. ETTER; MICHAEL R. CHASE; MICHAEL A. REX; ELIZABETH E. BOYLE (Molecular Ecology, 2006)
The deep‐sea soft‐sediment environment hosts a diverse and highly endemic fauna of uncertain origin. We know little about how this fauna evolved because geographic patterns of genetic variation, the essential information for inferring patterns of population differentiation and speciation are poorly understood. Using formalin‐fixed specimens from archival collections, we quantify patterns of genetic variation in the protobranch bivalve Deminucula atacellana, a species widespread throughout the Atlantic Ocean at bathyal and abyssal depths. Samples were taken from 18 localities in the North American, West European and Argentine basins. A hypervariable region of mitochondrial 16S rDNA was amplified by polymerase chain reaction (PCR) and sequenced from 130 individuals revealing 21 haplotypes. Except for several important exceptions, haplotypes are unique to each basin. Overall gene diversity is high ( h = 0.73) with pronounced population structure (Φ ST = 0.877) and highly significant geographic associations ( P 0.0001). Sequences cluster into four major clades corresponding to differences in geography and depth. Genetic divergence was much greater among populations at different depths within the same basin, than among those at similar depths but separated by thousands of kilometres. Isolation by distance probably explains much of the interbasin variation. Depth‐related divergence may reflect historical patterns of colonization or strong environmental selective gradients. Broadly distributed deep‐sea organisms can possess highly genetically divergent populations, despite the lack of any morphological divergence.

Identification and enumeration of bacteria assimilating dimethylsulfoniopropionate (DMSP) in the North Atlantic and Gulf of Mexico - Rex R. Malmstrom; Ronald P. Kiene; David L. Kirchman (Limnology and Oceanography, 2004)
The algal‐derived compound dimethylsulfoniopropionate (DMSP), which is the precursor of the climatically active gas dimethylsulfide, is potentially an important source of carbon and sulfur to marine bacterioplankton. Currently, bacteria of the Roseobacter clade, a subgroup of ά;‐proteobacteria, are hypothesized to be the key participants in the metabolism of DMSP. To test this hypothesis, we used a combination of microautoradiography and fluorescence in situ hybridization (Micro‐FISH) to identify the bacteria assimilating 35 S DMSP in the Gulf of Mexico, the Gulf of Maine, and the Sargasso Sea. On average, half of the bacterial community assimilated DMSP in these environments. Members of the ά‐proteobacteria dominated DMSP assimilation, accounting for 35–40% of bacteria assimilating DMSP. Cytophaga ‐like bacteria andγ‐proteobacteria each accounted for 15–30% of DMSP‐assimilating cells. The ά‐proteobacteria accounted for a greater fraction of the DMSP‐assimilating community than expected based on their overall abundance, whereas Cytophaga ‐like bacteria were typically underrepresented in the DMSP‐assimilating community. Members of the Roseobacter clade assimilated more DMSP on a per‐cell basis than any other group, but they did not account for most of the DMSP assimilation, nor were they always present even when DMSP turnover was high. These results indicate that the biogeochemical flux of dissolved DMSP is mediated by a large and diverse group of heterotrophic bacteria.

Extreme mitochondrial DNA divergence within populations of the deep-sea gastropod Frigidoalvania brychia - Quattro J.; Chase M.; Rex M.; Greig T.; Etter R. (Marine Biology, 2001)

A Comparison of Match Ozonesonde-Derived and 3D Model Ozone Loss Rates in the Arctic Polar Vortex during the Winters of 1994/95 and 1995/96 - I. Kilbane-Dawe; N. R. P. Harris; J. A. Pyle; M. Rex; A. M. Lee; M. P. Chipperfield (Journal of Atmospheric Chemistry, 2001)

Characteristics of human dendritic cells generated in a microgravity analog culture system - Cherylyn A. Savary; Monica L. Grazziutti; Donna Przepiorka; Stephen P. Tomasovic; Bradley W. McIntyre; Darren G. Woodside; Neal R. Pellis; Duane L. Pierson; John H. Rex (In Vitro Cellular & Developmental Biology - Animal, 2001)

A landscape approach to conserving wetland bird habitat in the prairie pothole region of eastern South Dakota - David E. Naugle; Rex R. Johnson; Michael E. Estey; Kenneth F. Higgins (Wetlands, 2001)

CHARACTERISTICS OF HUMAN DENDRITIC CELLS GENERATED IN A MICROGRAVITY ANALOG CULTURE SYSTEM - CHERYLYN A. SAVARY; MONICA L. GRAZZIUTTI; DONNA PRZEPIORKA; STEPHEN P. TOMASOVIC; BRADLEY W. McINTYRE; DARREN G. WOODSIDE; NEAL R. PELLIS; DUANE L. PIERSON; JOHN H. REX (In Vitro Cellular & Developmental Biology - Animal, 2001)

A landscape approach to conserving wetland bird habitat in the Prairie Pothole Region of eastern South Dakota - David E. Naugle; Rex R. Johnson; Michael E. Estey; Kenneth F. Higgins (Wetlands, 2000)

AC Stampede Russet: A high-yielding oblong russet cultivar for the french fry and fresh market industries - D. R. Lynch; J. C. Miller; L. M. Kawchuk; C. A. Schaupmeyer; J. Holley; J. Panford; D. K. Fujimoto; D. Waterer; J. Wahab; B. Rex; M. S. Goettel (American Journal of Potato Research, 2000)

Desulfotomaculum genus‐ and subgenus‐specific 16S rRNA hybridization probes for environmental studies - Krassimira R. Hristova; Margit Mau; Dandan Zheng; Rustam I. Aminov; Roderick I. Mackie; H. Rex Gaskins; Lutgarde Raskin (Environmental Microbiology, 2000)
Based on comparative analysis of 16S rRNA sequences and the recently established phylogeny of the genus Desulfotomaculum , a set of phylogenetically nested hybridization probes was developed and characterized. A genus‐specific probe targets all known Desulfotomaculum species (with the exception of Desulfotomaculum acetoxidans ), and five specific probes target subclusters within the Desulfotomaculum genus. The dissociation temperature of each probe was determined experimentally. Probe specificities were verified through hybridizations with pure culture rRNA isolated from a wide variety of target and non‐target organisms and through an evaluation of probe ‘nesting’ using samples obtained from four different environments. Fixation and hybridization conditions for fluorescence in situ hybridizations were also optimized. The probes were used in quantitative membrane hybridizations to determine the abundance of Desulfotomaculum species in thermophilic anaerobic digesters, in soil, in human faeces and in pig colon samples. Desulfotomaculum rRNA accounted for 0.3–2.1% of the total rRNA in the digesters, 2.6–6.6% in soil, 1.5–3.3% in human faeces and 2.5–6.2% in pig colon samples.

Temporal distribution of waterfowl in eastern South Dakota: Implications for aerial surveys - David E. Naugle; Rex R. Johnson; Thomas R. Cooper; Matthew M. Holland; Kenneth F. Higgins (Wetlands, 2000)

Chemical Ozone Loss in the Arctic Winter 1994/95 as Determined by the Match Technique - M. Rex; P. Von Der Gathen; G.O. Braathen; N.R.P. Harris; E. Reimer; A. Beck; R. Alfier; R. Krüger-carstensen; M. Chipperfield; H. De Backer; D. Balis; F. O'Connor; et al. (Journal of Atmospheric Chemistry, 1999)

Bias in quadrat-derived estimates of number of prairie wetlands - Rex R. Johnson; Kenneth F. Higgins (Wetlands, 1998)

Bathymetric patterns of genetic variation in a deep-sea protobranch bivalve, Deminucula atacellana - M. R. Chase; R. J. Etter; M. A. Rex; J. M. Quattro (Marine Biology, 1998)

A Study of Ozone Laminae Using Diabatic Trajectories, Contour Advection and Photochemical Trajectory Model Simulations. - S. J. Reid; M. Rex; P. Von Der Gathen; I. Fløisand; F. Stordal; G. D. Carver; A. Beck; E. Reimer; R. Krüger-Carstensen; L. L. De Haan; G. Braathen; V. Dorokhov; et al. (Journal of Atmospheric Chemistry, 1998)

Amisk: A clonal variant of Ranger Russet - D. R. Lynch; L. M. Kawchuk; C. A. Schaupmeyer; J. Holley; D. Waterer; B. L. Rex; M. K. Pritchard; J. Panford (American Journal of Potato Research, 1995)

AC Ptarmigan: An early maturing potato cultivar with good chipping and fresh market quality - D. R. Lynch; C. Schaupmeyer; L. M. Kawchuk; T. R. Tarn; B. Rex; J. Holley; D. Waterer; J. Panford; M. K. Pritchard (American Journal of Potato Research, 1994)

Niska: A maincrop chipping potato cultivar with high specific gravity and good quality after storage - D. R. Lynch; D. Kichefski; S. Peloquin; C. S. Schaupmeyer; L. la Croix; D. Waterer; Wm. T. Andrew; J. Holley; N. Crowe; B. McConnell; G. A Nelson; B. Rex (American Journal of Potato Research, 1991)

The effect of spacing of seedpieces on yield, quality and economic value for processing of Shepody potatoes in Manitoba - B. L. Rex; W. A. Russell; H. R. Wolfe (American Journal of Potato Research, 1987)

Videomicroscopic method for direct determination of blood flow to the papilla of the kidney - Rex L. Jamison; Bernd Zimmerhackl; Channing R. Robertson (Annals of Biomedical Engineering, 1985)

The source of inulin in samples of vasa recta blood - Paul A. Johnston; Frank B. Lacy; Veeraf M. Sanjana; Channing R. Robertson; Rex L. Jamison (Annals of Biomedical Engineering, 1977)